2020
DOI: 10.1001/jamainternmed.2019.5145
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Public Comments Submitted to State Health Technology Assessment Programs in Oregon and Washington

Abstract: reports receiving compensation fromMcKinsey & Company for providing strategy consulting to hospitals, insurance companies, and pharmaceutical companies on issues unrelated to this article.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…We also examined the citation of scientific evidence, adding to literature documenting lack of scientific evidence in public comments in other contexts. 10 The raw data from this study are available publicly, so that readers can view specific financial ties, evidence cited or reanalyse the data if desired. Finally, the AI/ML regulatory framework is still under development, and these findings may motivate better disclosure and use of scientific evidence as it continues to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined the citation of scientific evidence, adding to literature documenting lack of scientific evidence in public comments in other contexts. 10 The raw data from this study are available publicly, so that readers can view specific financial ties, evidence cited or reanalyse the data if desired. Finally, the AI/ML regulatory framework is still under development, and these findings may motivate better disclosure and use of scientific evidence as it continues to be developed.…”
Section: Discussionmentioning
confidence: 99%
“…We used a thorough method for identification of financial ties which has identified more potentially conflicted parties than would be apparent from the self-identification of the commenters. We also examined the citation of scientific evidence, adding to literature documenting lack of scientific evidence in public comments in other contexts 10 . The raw data from this study is available publicly, so that readers can view specific financial ties, evidence cited, or reanalyse the data if desired.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study from the United States demonstrated that financial conflicts of interest might also extend to patient representatives and advocacy groups [ 5 ]. These challenges, among others, translate into a growing skepticism for the reported benefit of new cancer drugs [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%